Effects Of Proposed Swimming Training Program For Enhancing Some Anaerobic Capacities Among 100-m Freestyle (9-12 Year Old) Junior Swimmers - Boudebza , Mostefa (sports creativity, 2025)
The study aimed to prepare a training program in the sport of swimming to improve some anaerobic abilities of the 100m free swimmers. The researcher relied this on the theories and references of "Magilcio", "Ossama Ratib" and "Abu Al-Ela Abdel Fattah". All of which indicate that the anaerobic threshold is of great importance in swimming training.This study was carried out to shed light on one of the four basic physical qualities or abilities (BPA) because of its importance in competitive swimming and its effect on improving the anaerobic capacity of the selected research group members in the baseline sample. From the research that has been undertaken on velocity-based training, it is possible to conclude that the proposed training program has a positive effect on developing the studied anaerobic capacity of 100-m freestyle trained swimmers and on increasing the responsiveness, interest-enjoyment and vitality of research sample.